Novel adiposity indices and their associations with all-cause and cardiovascular mortality in individuals with cardiovascular–kidney–metabolic syndrome stages 0–3: findings from a nationwide prospective cohort study - Zhou, Hangyu; Xing, Yingying; Wang, Tingting; Wang, Tiantian; Xierzhati, Saiyaremu; Adili, Diliyaer; Wang, Zhao; Li, Jie (Frontiers in Endocrinology, 2025)
BackgroundExcess visceral fat drives CKM syndrome. This study assessed how newer obesity measures relate to death risk in early CKM (stages 0-3).MethodsThis study included 26,899 participants with CKM stages 0–3 from the NHANES conducted between 2001 and 2018. Participants were grouped according to their baseline measurements of the adiposity indices (WWI, ABSI, WHtR, C-index, BRI, and BMI), which served as the exposure variables. Cox models, RCS curves, and two-stage Cox analyses were used to assess how novel obesity indices relate to mortality in this population. Subgroup analyses and sensitivity analyses evaluated risk differences across demographic groups and the robustness of the results. AUC, continuous NRI and IDI were used to compare the predictive performance of the novel indices and BMI for mortality.ResultsThe final analysis included a total of 26,899 participants. At the baseline, the gender distribution was 51.08% male, with an average age of 45.39 years. Compared with the lowest quartile group, the mortality rate was higher in the higher levels of the new obesity index groups.Novel indices significantly increased the risk of mortality. WWI showed the strongest link to all-cause death (HR:1.41, 95%CI:1.31 - 1.51) and cardiovascular death (HR 1.66,95%CI:1.39 - 1.99). ABSI, WWI, WHtR, and C-index had linear positive relationships with mortality. In contrast, BMI, BRI, and WHtR showed U-shaped associations with all-cause death (higher risk at both low and high values). The increased death risk linked to the new indices was greater in people aged 20–59 than in those ≥60. The incorporation of novel obesity biomarkers into the fully adjusted model significantly improved the predictive performance for adverse outcomes, as demonstrated by WWI, ABSI, and C-index. The continuous NRI values for these indices were 0.1831 (95% CI: 0.1289–0.1992), 0.2191 (0.1644–0.2877), and 0.1805 (0.1173–0.2398), with corresponding IDI values of 0.0356 (0.0193–0.0569), 0.0572 (0.0365–0.0839), and 0.0245 (0.0118–0.0432), respectively.ConclusionNovel obesity index is closely associated with mortality risk in the early CKM population. Novel indices offer superior obesity assessment and mortality prediction in early CKM compared to BMI.